La obstucalización e impedimiento del régimen de visitas por parte del progenitor custodio, en la ciudad de Machala, provincia de el Oro, durante el periodo comprendido al año 2013. - Solano Rubio, Susy Cecibel (2014)
This thesis makes the analysis of the obstacle or hindrance of visitation in Ecuador, for in our legislation there is no penalty for the parent who violates the resolution that visitation is set.